Implementasi Manajemen Jaringan MikroTik Layanan Port API Dengan Algoritma Hierarchial Tocken Bucket - Ari Ramadhan; Dadang Iskandar Mulyana; Yuma Akbar (Progresif: Jurnal Ilmiah Komputer, 2023)
The uncertain number of users connected to a wireless internet service is a problem for the quality of service, either in the form of frequent disconnections, slowness, and various other problems. The application of the MikroTik Userman plugin facility can be a solution to internet service problems, but Userman, which is the default for MikroTik, has limitations, so Mikhmon is a solution in Hotspot network management when there is a network to be properly managed and monitored. At this writing, we take advantage of features that are rarely used in general, implementing them first in a test lab, by creating a small-scale hotspot network but with the same management as a large-scale network. The result is that each client gets normal bandwidth of 2/2Mbps, 30Gb data quota, and 50 user shares, and the bandwidth will change dynamically every time a new user is added.Keywords: MikroTik; Hotspot; Application Programming Interface; Hierarchical Token Bucket; MikhmonAbstrakTidak menentunya jumlah pengguna yang terhubung pada suatu layanan wireless internet, menjadi permasalahan bagi kualitas layanan, baik berupa koneksi yang sering terputus,  lambat,  dan  berbagai masalah lain. Penerapan fasilitas plugin MikroTik Userman dapat menjadi solusi permasalahan layanan internet, namun Userman yang menjadi default dari MikroTik memiliki keterbatasan, sehingga Mikhmon menjadi solusi dalam manajemen jaringan Hotspot ketika ada jaringan yang akan diatur dan dimonitoring dengan baik. Pada penulisan ini, kami memanfaatkan fitur-fitur yang jarang digunakan secara umum, mengimplementasikannya terlebih dahulu pada lab uji coba, dengan membuat jaringan hotspot berskala kecil namun dengan manajemen yang sama seperti jaringan berskala besar. Hasil setiap client mendapatkan bandwith normal 2/2Mbps, Quota data 30Gb, dan share user sebanyak 50 user, dan bandwith akan berubah secara dinamis setiap ada penambahan user yang baru.Keywords: MikroTik; Hotspot; Application Programming Interface; Hierarchical Token Bucket; Mikhmon